Effect of Brewing Process and Sugar Content on 5-Hydroxymethylfurfural and Related Substances From Turkish Coffee - Mortas, M.; Gül, O.; Yazici, F.; Dervişoĝlu, M. (Taylor and Francis Inc. 325 Chestnut St, Suite 800 Philadelphia PA 19106, 2017)
The effect of brewing process on 5-hydroxymethylfurfural, 2-furylmethylketone, and 2-furoic acid levels of traditionally prepared and instant Turkish coffee samples containing different amounts of table sugar (0, 2, 4, or 8 g in 20 mL of coffee) were analyzed by high pressure liquid chromatography with diode array detector. The highest change at the levels of furfurals was observed in sample of traditional and instant Turkish coffee named T4 and S4 both of containing 8 g of sugar, respectively. The results showed that 5-hydroxymethylfurfural, 2-furylmethylketone, and 2-furoic acid concentrations in both traditionally prepared and instant Turkish coffee samples increased with increasing sugar concentration. The brewing method and sugar concentration had a significant effect on furfural contents of Turkish coffee (p < 0.05). Daily intakes of furfurals for Turkish population were calculated as 8.14–13.54 and 9.36–10.25 µg kg−1 body weight for traditionally prepared and instant Turkish coffee samples, respectively, and daily intakes of furfurals were lower than the acceptable daily intake value of 0.5 mg kg−1 body weight. © 2017 Taylor & Francis Group, LLC.
Keywords: 2-Furoic Acid; 2-Furylmethylketone; 5-Hydroxymethylfurfural; Brewing; Dietary Intake